MANAJEMEN SUMBER DAYA AIR DI LOMBOK TIMUR: DEFISIT AIR DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Kabul, Lalu Muh.; Ahyat, Muhamad (Sekolah Tinggi Ilmu Ekonomi AMM Mataram, 2018)
Regarding water resources management, the research carried out in order to study various factors affected water deficit that occurred in East Lombok. The research method was quantitative approach namely factor analysis. Data sources were primary and secondary data. For data collecting used interview and FGD. Kaiser-Meyer-Olkin (KMO’s test), Bartlett’s test, anti image Correlation, Eigenvalue, Force Field Analysis were tools employed to analyze the data. The research results were two factors that affected water deficit namely forest destruction and institution. Forest conservation at the up stream area was a strategy to overcome the forest destruction, and strengthening capacity of the P3A and creating the Multistakeholder was a strategy to overcome the institution factor.